Effect of sweet almond suspension as anti-inflammatory in experimental infected mice with arthritis: Lubna A. Kafi and Yousif Z. A. AL – Zobahi - Kafi, Lubna A. (The Iraqi Journal of Veterinary Medicine, 2012)
The current study was conduct to determine the effects of oral treatment of sweet Almond Suspension (SAS) on induced arthritis by Incomplete Freund’s Adjuvant (IFA).Seventy mice, with close age and weight were used; they were equally divided in to 7 groups (10 mice per group). The first group served as negative control (non infected – non treated (NINTC). The second group was the positive control (infected non treated, (NINTC) the third and fourth groups were those treated with 1.42 or 2.84 g/kg of SAS respectively. The fifth group was treated with voltarin (ITV), while the sixth and seventh groups were treated with the same closes of SAS but before infection (Prophylactic infected groups, PI1, PI2).The size of knee joint, carrageenan test, level of alkaline phosphatase and histopathological changes in the knee joint used as parameters to compare between groups. The results showed that SAS was able to subside signs of arthritis by decreasing the size of knee and decrease the formation of edema which was induced by injection of carrageenan in the paw of the animal, Histopathological study showed that joints of treated groups by SAS had no signs of arthritis. However, there was slight infiltration of netrophile in treatment and prophylactic group.